2012
DOI: 10.1007/s00405-012-2259-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenoid biofilm in chronic otitis media with effusion in children

Abstract: To study the extent of surface adenoid biofilm and to evaluate its role in the pathogenesis of chronic otitis media with effusion (COME) in children. The study was carried out on 100 children between 3 and 14 years of age, who were divided into two groups. The first group (50 children) had otitis media with effusion associated with adenoid hypertrophy, whereas the second group (50 children) had adenoid hypertrophy without middle ear effusion. Adenoidectomy with ventilation tube insertion was done for group 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 21 publications
2
40
0
3
Order By: Relevance
“…Our results are similar with other presented in a large number of studies indicating that adenoidectomy is effective in the treatment of COME and CRS, having in mind that adenoids act as a reservoir of pathogenic bacteria and play an important role in the pathogenesis of these two conditions [13,[20][21][22].…”
Section: Discussionsupporting
confidence: 95%
“…Our results are similar with other presented in a large number of studies indicating that adenoidectomy is effective in the treatment of COME and CRS, having in mind that adenoids act as a reservoir of pathogenic bacteria and play an important role in the pathogenesis of these two conditions [13,[20][21][22].…”
Section: Discussionsupporting
confidence: 95%
“…Linder et al [28] also reached to the same conclusion. Saafan et al [29] conducted a study to determine the role of bacterial biofilm pathogenesis on developing OME. Using both culture and polymerase chain reaction (PCR) techniques, they found that adenoid samples from children with middle ear effusion had higher grade biofilm formation than those without effusion.…”
Section: Resultsmentioning
confidence: 99%
“…These three-dimensional communities of bacteria, attached to a surface, encased in self-produced extracellular matrix, and with altered phenotype, are thought to exert a chronic inflammatory stimulus leading to OME. Chronic biofilm colonization of the adenoids may act as a reservoir for bacteria entering the middle ear cleft in OM 36. The overexpression of mucin genes is also exacerbated by cigarette smoke 37.…”
Section: Etiologymentioning
confidence: 99%